2012
DOI: 10.1063/1.4742979
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of lead and titanium into a porous alumina membrane during Pb(Zr0.52Ti0.48)O3 nanotube synthesis

Abstract: Size-dependent emission efficiency and luminescence characteristics of YBO3:Tb3+ nanocrystals under vacuum ultraviolet excitations J. Appl. Phys. 112, 054321 (2012) Photoluminescence from GaAs nanodisks fabricated by using combination of neutral beam etching and atomic hydrogen-assisted molecular beam epitaxy regrowth Appl. Phys. Lett. 101, 113108 (2012) Characterization of thiol-functionalized oligo(phenylene-ethynylene)-protected Au nanoparticles by scanning tunneling microscopy and spectroscopy Appl. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The volatility of PbO is also a recurring issue. In contrast, it was shown that annealing temperatures up to 700°C carry enough energy to induce Pb diffusion into AAO through oxygen vacancies 32 . This phenomenon may thus promote crystallized interphases formation of Pb2Al2O5, PbAl12O19 or Al2TiO5 (Fig.…”
Section: = % % ( + + )mentioning
confidence: 97%
“…The volatility of PbO is also a recurring issue. In contrast, it was shown that annealing temperatures up to 700°C carry enough energy to induce Pb diffusion into AAO through oxygen vacancies 32 . This phenomenon may thus promote crystallized interphases formation of Pb2Al2O5, PbAl12O19 or Al2TiO5 (Fig.…”
Section: = % % ( + + )mentioning
confidence: 97%